Effects of neodymium and gadolinium on weathering resistance of ZnO-B2O3-SiO2 glass - 李雄伟 李梅 王觅堂 柳召刚 胡艳宏 田俊虎 (Journal of rare earths, 2014)
The ZnO-B203-SiO2 glass doped with Nd2O3 and Gd2O3 was prepared by high temperature melt cooling method. The standard sample of the zinc borosilicate glass was placed in the constant temperature and humidity chamber in order to simulate the atmospheric corrosion process. The surface of the weathered glass was analyzed by scanning electron microscope and energy disper- sive spectrometry and the filtrate was analyzed by inductively coupled plasma-atomic emission spectrometry. The results showed that humidity was the most important factor influencing weathering; the morphology of glass surface of altered layer and the product on the surface was observed; the corroding degree of the zinc borosilicate glass doped with Nd or Gd was significantly lighter than that of the base glass. Adding rare earth Nd or Gd in the zinc borosilicate glass could suppress Na, Zn, Si ion release in weathering.